A Systematic Literature Review of the Significance of the School of Living Tradition in the Preservation of Cultural Heritage of the Indigenous Peoples - Hipolito, Mark Floricar G. (Future Science / FSH-PH Publications, 2024)
This systematic literature review investigates the critical role of the School of Living Traditions (SLT) and its educational approaches in preserving the cultural heritage of Indigenous Peoples (IP) in the Philippines. A set of pre-defined inclusion-exclusion criteria led to the selection of six pertinent papers, which were comprehensively analyzed and synthesized. The examination of these articles revealed recurring themes, allowing for the development of thematic constructs to address the study's objectives. The findings underscore the pivotal role of SLTs in safeguarding the profound traditions of Indigenous Peoples, thereby ensuring the transmission of cultural legacies to younger generations and empowering IP communities. Notably, the significance of SLTs lies in their ability to preserve the authentic essence of cultural practices, contributing to the empowerment of Indigenous communities. In the transmission of this indigenous knowledge, systems, and practices, pedagogical approaches within SLTs are centered on culture-based education and experiential learning. These approaches aim to facilitate meaningful learning experiences that enable individuals to derive personal significance from their acquired knowledge and apply it in real-world contexts. Consequently, this research sheds light on the instrumental role of SLTs in fostering cultural preservation and empowerment within Indigenous communities through tailored educational methodologies.